Early Predictors of the Response to Adalimumab Therapy in Patients With Juvenile Idiopathic Arthritis Without Systemic Manifestations: A Prospective Cohort Study - Ekaterina I. Alexeeva; Tatyana M. Dvoryakovskaya; Kseniya B. Isaeva; Tatyana V. Sleptsova; Rina V. Denisova; Margarita A. Soloshenko; Olga L. Lomakina; Anna N. Fetisova; Mariya G. Rudnickaya; Dariya D. Vankova; Yuri M. Dyakonov; Alina A. Alshevskaya; et al. ("Paediatrician" Publishers LLC, 2018)
Background. Tumour necrosis factor alpha inhibitors are widely used in the treatment  of juvenile idiopathic arthritis (JIA). To achieve maximum efficiency of genetically engineered biologic drugs, it is necessary to study predictors of the response to therapy. Objective. Our aim was to identify early predictors  of the response  to adalimumab therapy in patients with JIA without systemic manifestations. Methods. A prospective cohort study analysed treatment results of patients with JIA without systemic manifestations, who were prescribed adalimumab for the period from August 2008 to August 2014. We studied the relationship between baseline demographic indicators as well as baseline and registered after one month of treatment clinical and laboratory parameters and the best (remission according to the Wallace criteria) response to therapy after one year. Results. In the first year of therapy, 94 (43.9%) of 214 patients achieved remission according to the Wallace criteria. In a multivariate analysis, predictors of achieving remission after one year of adalimumab therapy were the improvement according to the ACR70 criterion after one month of therapy [odds ratio (OR) 3.3; 95% confidence interval (CI) 1.7-6.7], a history of uveitis (OR 1.86; 95% CI 1.03-3.33), a decrease in the number of joints with active arthritis after one month of therapy (OR 1.09; 95% CI 1.02-1.16). During therapy, injection reactions in the form of pain were observed in 36 (16.8%) of 214 patients, infectious diseases of ENT organs - in 85 (39.7%), of the respiratory tract - in 17 (7.9%), and tubinfection - in 13 (6.1%) children. Conclusion. The presence of uveitis, rapid reduction in the number of joints with active arthritis and a high level of response to treatment after one month of adalimumab therapy are predictors for achieving remission during the first year of treatment.